Macroprudential FX regulations: Shifting the snowbanks of FX vulnerability? - Toni Ahnert; Kristin Forbes; Christian Friedrich; Dennis Reinhardt (Bank of Canada, 2018)
Can macroprudential foreign exchange (FX) regulations on banks reduce the financial and macroeconomic vulnerabilities created by borrowing in foreign currency? To evaluate the effectiveness and unintended consequences of macroprudential FX regulations, we develop a parsimonious model of bank and market lending in domestic and foreign currency and derive four predictions. We confirm these predictions using a rich data set of macroprudential FX regulations. These empirical tests show that FX regulations (1) are effective in terms of reducing borrowing in foreign currency by banks; (2) have the unintended consequence of simultaneously causing firms to increase FX debt issuance; (3) reduce the sensitivity of banks to exchange rate movements; but (4) are less effective at reducing the sensitivity of corporates and the broader financial market to exchange rate movements. As a result, FX regulations on banks appear to be successful in mitigating the vulnerability of banks to exchange rate movements and the global financial cycle, but partially shift the snowbank of FX vulnerability to other sectors.
Keywords: F32; F34; G15; G21; G28; 330; Financial system regulation and policies; Exchange rates; Financial institutions; International financial markets